2013
DOI: 10.1016/j.bbmt.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Invasive Fungal Disease after Allogeneic Hematopoietic Stem Cell Transplantation: A Single Center Experience

Abstract: Invasive fungal disease (IFD) is a major cause of morbidity and mortality after hematopoietic stem cell transplantation (HCT). We performed a retrospective review of 271 adults with a hematologic malignancy undergoing allogeneic HCT to determine the incidence of and risk factors for IFD and to examine the impact of IFD on nonrelapse mortality and overall survival. We defined IFD using standard criteria and selected proven and probable cases for analysis. Diagnoses in the study group included acute leukemia (42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 59 publications
4
43
0
3
Order By: Relevance
“…Multiple factors reported to be associated with the risk of IFI include donor type, conditioning regimens, prolonged neutropenia, GVHD, and highdose corticosteroids (Fukuda et al, 2003;Thursky et al, 2004;Ozyilmaz et al, 2010;Omer et al, 2013). According to our data, we found similar risk factors infecting IFI.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Multiple factors reported to be associated with the risk of IFI include donor type, conditioning regimens, prolonged neutropenia, GVHD, and highdose corticosteroids (Fukuda et al, 2003;Thursky et al, 2004;Ozyilmaz et al, 2010;Omer et al, 2013). According to our data, we found similar risk factors infecting IFI.…”
Section: Discussionsupporting
confidence: 75%
“…Previously identified risk factors of IFI include donor type, GVHD, high-dose corticosteroids, increased ferritin levels, and so on (Fukuda et al, 2003;Thursky et al, 2004;Ozyilmaz et al, 2010;Omer et al, 2013). Epidemiology and risk factors of IFI differ due to the changes in antifungal prophylaxis and treatment in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles have already suggested that the development of acute GvHD is a risk factor for opportunistic infection, such as invasive fungal disease and CMV reactivation. 15,19,28 Our previous study also suggested that although the incidence of grade 2-4 acute GvHD was similar between haploidentical HSCT and HLA-identical sibling HSCT, the incidence of grade 1-4 acute GvHD was significantly higher after haploidentical HSCT than after HLA-identical sibling HSCT (Po0.0001) that increased the use of immunosuppressive agents after haploidentical HSCT compared with HLA-identical sibling HCST; this course finally led to an increased incidence of infection. 21 Therefore, the cause of mortality for patients who had both GvHD and infection was classified according to the main and direct causes of mortality in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous studies suggested that compared with HLA-identical sibling HSCT, haploidentical HSCT increased the incidence of invasive fungal disease (7.1% vs 3.3%, P = 0.007), post transplant lymphoproliferative disease (2.3% vs 0.4%, Po0.05) and CMV disease (8.7% vs 0.0%, P = 0.004) [15][16][17] that are usually associated with a higher risk of mortality after transplant. [16][17][18][19] Moreover, our previous study found that the T-cell subset and dendritic cell subgroup counts, especially CD8 + , CD4 + and CD4 + naive T cells, within the first 90 days post transplant were significantly lower in patients receiving haploidentical HSCT than in HLA-identical sibling HSCT (Po0.05). 20 As a result, the early delayed immune reconstitution after haploidentical HSCT probably led to an increased incidence of infection and infection-related mortality post transplant and finally led to a higher incidence of TRM.…”
Section: Discussionmentioning
confidence: 99%
“…espite advances in treatment and supportive care, invasive aspergillosis (IA) is associated with significant morbidity and mortality rates, especially among patients with hematologic malignancies and hematopoietic stem cell transplant (HSCT) recipients (1,2). Systemic antifungal prophylaxis is widely used in this patient population (3,4), and patients with recurrent or persistent fever and prolonged neutropenia frequently require empirical coverage with antifungal agents (5).…”
mentioning
confidence: 99%